Brief report on the germ heat-resistance-lowering by adding polyphosphate salts in meat products - ΒΑΤΣΟΣ ΕΥΑΓ. ΑΠ. (Journal of the Hellenic Veterinary Medical Society, 2019)
1. The heat-resistance-lowering effect of disodiumdiphosphate, sodiumtripolyphosphate and trisodiumcitrate on Lactobacillus helveticus, Bacillus cereus and Clostridium sporogenes in Frankfurter-type sausages and cooked ham was examined. 2. During the heat-treatment of Frankfurter-type sausages, oligophosphates promoted the killing of the examined germs. A specific retarding-effect at a storage temperature of 15° C was not observed. The influence ascertained for test-germs was also reflected in the sum total of germs in the product. Diphosphates had a somewhat stronger effect in lowering heat-resistance. The replacement of NPS by NaCl yielded no differences in any of the cases. 3. Sodiumtripolyphosphate and trisodiumcitrate had a clearly heat-resistance-lowering effect in cooked ham, but not a growth-retarding effect on the examined germs. The influence on the test-germs was also reflected in the sum total of germs in the product. 4. As was expected, the water content was somewhat higher in the case of the phosphatehams, the raw protein and fat content somewhat lower. 5. The losses through boiling were, in general, relatively high because the hams were not tumbled. The losses in the case of the sodiumtriphosphate-charge were somewhat lower than in the cases of the others. 6. The color, consistency and taste ratings of the cooked hams produced with sodiumtripolyphosphate were strikingly favourable.